Islamophobia and Media Framing in West Media - Nikmah Suryandari; Syamsul Arifin (Institut Agama Islam Negeri Madura, 2021)
The focus of this article is to explain the lousy illustration of Islam and Muslims in international media. The media worldwide is considered the most influential medium that’s formed the views of human beings related to each phase of societies. The media carry out a massive position in building the listener perspective and mindset related to any problem that emerges within the whole globe. In this context, the audiences take delivery as genuine. They expect from media to symbolize a clean photo relate to any affair which is taking place at each countrywide and international floor. In western media, Muslims are represented as an “other alien” on a global level. After September 11, Muslims and Islam have recognized as backward and violent traditions and faith. Muslim communities and their households are generally sufferers and focused via non-Muslims, victimization of a veiled Muslim girl and religious guys in public locations, as victims and targeted against the law. In gift days, Islam and Muslims are represented as a terrorist, illiterate, extremist and backward in global media. Although the framing of Muslims and Islam, mainly after the 7/7 bombing, September 11 terrorist assault, and Paris assault, a massive number of look at and research installation, that the world over the inclination of media reporting is exceedingly located negativity in the direction of Islam and Muslims, through affiliating it with extremism and terrorism.